Recognition of Yeast mRNAs as “Nonsense Containing” Leads to Both Inhibition of mRNA Translation and mRNA Degradation: Implications for the Control of mRNA Decapping - Muhlrad, Denise (The American Society for Cell Biology, 1999)
A critical step in the degradation of many eukaryotic mRNAs is a decapping reaction that exposes the transcript to 5′ to 3′ exonucleolytic degradation. The dual role of the cap structure as a target of mRNA degradation and as the site of assembly of translation initiation factors has led to the hypothesis that the rate of decapping would be specified by the status of the cap binding complex. This model makes the prediction that signals that promote mRNA decapping should also alter translation. To test this hypothesis, we examined the decapping triggered by premature termination codons to determine whether there is a down-regulation of translation when mRNAs were recognized as “nonsense containing.” We constructed an mRNA containing a premature stop codon in which we could measure the levels of both the mRNA and the polypeptide encoded upstream of the premature stop codon. Using this system, we analyzed the effects of premature stop codons on the levels of protein being produced per mRNA. In addition, by using alterations either in cis or in trans that inactivate different steps in the recognition and degradation of nonsense-containing mRNAs, we demonstrated that the recognition of a nonsense codon led to a decrease in the translational efficiency of the mRNA. These observations argue that the signal from a premature termination codon impinges on the translation machinery and suggest that decapping is a consequence of the change in translational status of the mRNA.